Gamificación digital y su impacto en el desarrollo cognitivo de los estudiantes de sexto año de EGB de la UE Isabela Católica, Babahoyo 2024-2025 - Villacis Chica, Victor Alexander (2025)
The main objective of this Curricular Integration Project was to determine how digital gamification impacted the cognitive development of 6th grade students of the Isabela Católica Educational Unit, Babahoyo. The problem addressed was: ¿How does digital gamification impact the cognitive development of students? The research adopted a mixed approach to analyze the impact of the study phenomenon, combining both quantitative and qualitative methods. Thus, it not only allowed to establish direct relationships between the use of gamification and cognitive performance, but also to capture how gamified strategies impact motivation, learning and concept assimilation. Therefore, the results obtained show a discrepancy between students' positive perception of gamification and the lack of effective implementation in the classroom. The study identified that, although gamification can be a powerful tool to capture students' attention and motivate them, its effectiveness depends on the design and contextualization of the activities. In addition, it was evidenced that a significant portion of students prefer interactive methods for learning, which justifies the need to strengthen the integration of digital strategies in teaching.